2019
DOI: 10.1002/ar.24232
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Human Dermal Fibroblast Heterogeneity in Autologous Dermal Fibroblast Therapy: An Overcomplicated Strategy or a Promising Approach?

Abstract: Although human dermal fibroblast heterogeneity has been acknowledged for several decades and a large body of in vitro studies has been performed with zonal dermal fibroblast, current autologous dermal fibroblast therapies do not reflect human dermal fibroblast heterogeneity. To determine if the utilization of human dermal fibroblast heterogeneity in autologous dermal fibroblast therapy is more of a translational perspective that may thus be more likely to make it to the clinic, this article critically reviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…We and others suggested that papillary fibroblasts are more pro-angiogenic compared to reticular (Sorrell et al 2008a;Nauroy et al 2017). However, the lack of physiologically relevant in vivo models has limited the understanding of the molecular and cellular mechanisms underlying these processes (Philippeos et al 2018;Zuo et al 2019). In vitro models are being extensively used but mostly consist in 2D cell monolayers or 3D hydrogels made of exogenous proteins (Sorrell et al 2004;Mine et al 2008;Varkey et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We and others suggested that papillary fibroblasts are more pro-angiogenic compared to reticular (Sorrell et al 2008a;Nauroy et al 2017). However, the lack of physiologically relevant in vivo models has limited the understanding of the molecular and cellular mechanisms underlying these processes (Philippeos et al 2018;Zuo et al 2019). In vitro models are being extensively used but mostly consist in 2D cell monolayers or 3D hydrogels made of exogenous proteins (Sorrell et al 2004;Mine et al 2008;Varkey et al 2013).…”
Section: Introductionmentioning
confidence: 99%